2015
DOI: 10.1123/jsr.2013-0056
|View full text |Cite
|
Sign up to set email alerts
|

Scapular Kinematics During Late Cocking of a Simulated Throwing Activity in Baseball Players With Shoulder Injury: A Cross-Sectional Study Using a 3D-to-2D Registration Technique

Abstract: Compared with that in the contralateral shoulder, scapular external rotation was smaller in the throwing shoulder, which would increase glenohumeral horizontal abduction during the arm-cocking phase and be related to the throwing-shoulder disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…A single experienced researcher embedded the local coordinate system of the glenoid and humerus onto the 3D bone models using the 3D-Aligner software (GLAB Corp., Higashihiroshima, Japan). Humerus coordinates were set with their origin at the center of the humeral head, a Y-axis parallel to the humeral shaft, and an X-axis passing through the center of the intertubercular groove [ 22 ]. Scapular coordinates were set with their origin at the center of the scapular glenoid cavity, a Y-axis parallel with a line connecting the topmost and lowermost edges of the glenoid cavity, and a Z-axis parallel to a line connecting the anterior-most and posterior-most edges of the glenoid cavity [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…A single experienced researcher embedded the local coordinate system of the glenoid and humerus onto the 3D bone models using the 3D-Aligner software (GLAB Corp., Higashihiroshima, Japan). Humerus coordinates were set with their origin at the center of the humeral head, a Y-axis parallel to the humeral shaft, and an X-axis passing through the center of the intertubercular groove [ 22 ]. Scapular coordinates were set with their origin at the center of the scapular glenoid cavity, a Y-axis parallel with a line connecting the topmost and lowermost edges of the glenoid cavity, and a Z-axis parallel to a line connecting the anterior-most and posterior-most edges of the glenoid cavity [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The RMS error observed in this study was an in-plane error of 0.12 mm and an out-of-plane error of 0.61 mm, which are comparable to previous validation studies. [23] Statistical Analysis…”
Section: Data Processingmentioning
confidence: 99%
“…High in-plane accuracy is a strong point of these techniques employing single-plane radiographic imaging, with a reported accuracy of 0.47 mm and 1.53 mm for in-plane and out-of-plane translations, respectively, and 0.76° and 3.72° for in-plane and out-ofplane rotations, respectively. [23] Previous studies [20,22] that used this method limited tear sizes to medium or large rotator cuff tears. None of the studies we found analyzed the effect of subscapularis tears on joint dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Scapula and humerus movements are multiplanar (3-dimensional [3D]), coupled and coordinated during arm elevation [12], and hence believed to be equally so during overhead throwing. Evaluations of 3D scapular kinematics in overhead throwers have thus evolved from simple humeral positioning in the frontal, sagittal, or scapular planes to humeral motion in the horizontal plane (shoulder internal/external rotation) with the arm at 90 • of abduction [13,14] and, ultimately, simulation of a throwing action [15][16][17][18]. In an overhead throw, the scapula appears to externally rotate, upwardly rotate, and posteriorly tilt during the early cocking phase of the cycle, progresses into internal rotation after maximum humeral horizontal abduction and reaches the highest posterior tilting at the late cocking phase (maximum humeral external rotation).…”
Section: Introductionmentioning
confidence: 99%